Analysis of Factors Influencing the Effectiveness of Group Leader Level Recruitment at PT Kalimantan Prima Persada - Rika Anggraini; Ratri Wahyuningtyas (Yayasan Aya Sophia Indonesia, 2025)
PT Kalimantan Prima Persada (KPP) faces challenges in achieving its Group Leader (GL) recruitment target, with only 60% of the 90% target achieved in 2022–2023. Large monthly fluctuations (9%–71%) indicate that the current recruitment strategy is ineffective and could hinder the company's expansion. This study aims to analyze the dominant factors influencing the effectiveness of GL recruitment at KPP, particularly in the highly competitive mining industry. The study used a quantitative explanatory approach using Exploratory Factor Analysis (EFA). Data were obtained through questionnaires administered to 136 respondents, consisting of 15 HR team members and 121 GL candidates. Ten initial variables measured using a Likert scale included recruitment sources, selection methods, employer branding, recruitment technology, user department involvement, organizational culture, compensation and benefits, company regulations, candidate experience, and candidate diversity. The EFA analysis revealed six key factors influencing recruitment effectiveness. The most dominant factors were the quality of internal recruitment and organizational culture, while second-highest-ranking factors included diversity, communication, and well-being. The study also found gaps in user department involvement and suboptimal candidate diversification. Based on these findings, several strategic recommendations were proposed: strengthening organizational culture and compensation systems, increasing user department involvement in the selection process, integrating AI-based recruitment technology, and developing employer branding that emphasizes candidate experience. This study provides an important contribution to understanding critical GL recruitment factors in the mining industry and opens up opportunities for further research by testing the model on other mining companies with similar characteristics.